2008
DOI: 10.1111/j.1365-2710.2008.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of inhaled steroids in children with non-cystic fibrosis bronchiectasis

Abstract: In this study, 12 week-withdrawal of inhaled steroid treatment resulted in a significant increase in bronchial hyperreactivity and decrease in neutrophil apoptosis, but no change in sputum inflammatory markers in children with non-CF bronchiectasis was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…HO et al [37] showed an improvement in a subgroup of patients with P. aeruginosa infection. Withdrawal of ICS after a 12-week course produced increased bronchial hyperreactivity and decreased neutrophil apoptosis but no other changes [38].…”
Section: Mannitol (Potential Future Treatment)mentioning
confidence: 82%
“…HO et al [37] showed an improvement in a subgroup of patients with P. aeruginosa infection. Withdrawal of ICS after a 12-week course produced increased bronchial hyperreactivity and decreased neutrophil apoptosis but no other changes [38].…”
Section: Mannitol (Potential Future Treatment)mentioning
confidence: 82%
“…[37] Evidence is insufficient to establish whether ICS are beneficial in CF, as withdrawal in a selected patient population already taking ICS has been shown to be safe. [38][39][40] However, the 12-week withdrawal of ICS treatment resulted in a significant increase in bronchial hyperreactivity and decrease in neutrophil apoptosis, but no change in sputum inflammatory markers in children with non-CF bronchiectasis, [41] suggesting a possible benefit of ICS treatment. However, as significant benefit of treatment with ICS has not been conclusively demonstrated, [39] this treatment is only recommended for a subgroup of patients with documented bronchial hyperreactivity.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…A Cochrane review of inhaled corticosteroids in children and adults with bronchiectasis identified no pediatric studies, and hence there is no available evidence to support their use (75). However, a small study of inhaled corticosteroid withdrawal over a 12-week period in 27 children with bronchiectasis (83) reported a significant increase in bronchial hyper-reactivity after ceasing the drug (37.0 vs 46.8%, p  = 0.016) and a decrease in neutrophilic apoptosis in induced sputum (42.8 vs 20.2%, p  = 0.03), but no change in sputum inflammatory markers or in the number of infectious exacerbations (83). Larger studies are required to confirm these findings and to determine whether they are of any clinical significance.…”
Section: Preventionmentioning
confidence: 99%